1998
DOI: 10.1074/jbc.273.15.8946
|View full text |Cite
|
Sign up to set email alerts
|

thiBPQ Encodes an ABC Transporter Required for Transport of Thiamine and Thiamine Pyrophosphate inSalmonella typhimurium

Abstract: In Salmonella typhimurium, thiamine pyrophosphate (TPP) is a required cofactor for several enzymes in central metabolism. Herein we identify a new thi operon, thiBPQ (designated sfuABC in Escherichia coli), required for the transport of thiamine and TPP into the cell. Insertions in the operon result in strains that are phenotypically and biochemically defective in thiamine and TPP transport. Data presented herein show that this operon is transcriptionally repressed in the presence of exogenous thiamine, with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 33 publications
1
76
0
Order By: Relevance
“…To determine the possible role of the thi box in gene expression, the E. coli genome was searched for the thi box sequence as detailed in Materials and Methods. Interestingly, the thi box sequence was found only in front of the three thiamin biosynthetic operons (thiCEFSGH, thiMD, and thiBPQ), whose expression in S. enterica has been shown to be negatively regulated by TPP (4,12,13). This correlation suggests that the thi box is a regulatory element involved in repression of gene expression by thiamin.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…To determine the possible role of the thi box in gene expression, the E. coli genome was searched for the thi box sequence as detailed in Materials and Methods. Interestingly, the thi box sequence was found only in front of the three thiamin biosynthetic operons (thiCEFSGH, thiMD, and thiBPQ), whose expression in S. enterica has been shown to be negatively regulated by TPP (4,12,13). This correlation suggests that the thi box is a regulatory element involved in repression of gene expression by thiamin.…”
Section: Resultsmentioning
confidence: 83%
“…In both organisms the thi genes are located throughout the chromosome and are arranged in three operons and four single gene loci (2). thiCEFSGH, thiMD (ThiM and ThiD are involved in salvage of 5-(2-hydroxyethyl)-4-methyl thiazole and 4-amino-5-hydroxymethyl-2-methyl pyrimidine from the culture medium, respectively; ThiD also catalyzes the phosphorylation of 4-amino-5-hydroxymethyl-2-methyl pyrimidine monophosphate and thiBPQ (which code for an ABC type transport system for thiamin and TPP) are the operons transcriptionally regulated by TPP, whereas the single loci are not regulated (4,12,13). Although some point mutations have been isolated that affect the transcriptional regulation of thi genes, they map at min 10 on the S. enterica chromosome and at least one of them is an allele of thiL gene encoding thiamin monophosphate kinase, suggesting that TPP is the effector molecule involved in regulation of thi gene expression (10,12).…”
mentioning
confidence: 99%
“…ABC-T SMc02509 was induced by both manganese and iron limitation (Ϸ110-fold) and is the identified manganese transporter (Sit) from S. meliloti (38). ABC-T SMc03869 was induced by thiamine limitation (11-fold) and has 57% identity with the characterized thiamine transporter (Thi) from S. typhimurium (39). ABC-T SMc03196, induced 12-fold by molybdate limitation, has 58% identity with the characterized molybdate transporter (Mod) from B. japonicum (40).…”
Section: Site the Results Are Shown In Full Inmentioning
confidence: 99%
“…HIMB59, thiC, thiD, thiG, thiE and thiE2 and thiS are absent. However, a gene encoding a thiamin-specific periplasmic binding protein (thiB) (Webb et al, 1998) was identified in HIMB59 (Table 1).…”
Section: Resultsmentioning
confidence: 99%